Has globalisation increased inequality? - Axel Dreher; Noel Gaston (ETH Zurich, KOF Swiss Economic Institute, 2006)
There has been no shortage of theories which purport to explain why globalisation may have, adverse, insignificant or even beneficial effects on income and earnings inequality. Surprisingly, the empirical realities remain an almost complete mystery. In this paper we use data on industrial wage inequality, household income inequality as well as measures of the economic, social and political dimensions of globalisation to examine this controversial issue. We find that the economic dimension of globalisation, and - less robustly - political integration, have exacerbated wage inequality in developed countries. In contrast, the impact of globalisation on both income and earnings inequality in less-developed countries has been negligible.
Keywords: F02; D30; O57; C82; 330; Income and earnings inequality; globalisation; democracy; panel regressions; Globalisierung; Einkommensverteilung; Demokratie; Schätzung